Notch3 is an asymmetric gene and a modifier of heart looping defects in Nodal mouse mutants. - Tobias Holm Bønnelykke; Marie-Amandine Chabry; Emeline Perthame; Gregor Dombrowsky; Felix Berger; Sven Dittrich; Marc-Phillip Hitz; Audrey Desgrange; Sigolène M Meilhac (PLoS Biology)
The TGFβ secreted factor NODAL is a major left determinant required for the asymmetric morphogenesis of visceral organs, including the heart. Yet, when this signaling is absent, shape asymmetry, for example of the embryonic heart loop, is not fully abrogated, indicating that there are other factors regulating left-right patterning. Here, we used a tailored transcriptomic approach to screen for genes asymmetrically expressed in the field of heart progenitors. We thus identify Notch3 as a novel left-enriched gene and validate, by quantitative in situ hybridization, its transient asymmetry in the lateral plate mesoderm and node crown, overlapping with Nodal. In mutant embryos, we analyzed the regulatory hierarchy and demonstrate that Nodal in the lateral plate mesoderm amplifies Notch3 asymmetric expression. The function of Notch3 was uncovered in an allelic series of mutants. In single neonate mutants, we observe that Notch3 is required with partial penetrance for ventricle thickness, septation and aortic valve, in addition to its known role in coronary arteries. In compound mutants, we reveal that Notch3 acts as a genetic modifier of heart looping direction and shape defects in Nodal mutants. Whereas Notch3 was previously mainly associated with the CADASIL syndrome, our observations in the mouse and a human cohort support a novel role in congenital heart defects and laterality defects.